IMPLEMENTASI SUPERVISI PENDIDIKAN DALAM MENINGKATKAN PROSES PEMBELAJARAN DI SEKOLAH DASAR - Fatma Dewi (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
A principal as a supervisor has to conduct supervision in his/her school. Hence he/she must be able to perform a variety of monitoring and control to improve the performance of teachers. Supervision and control are preventive ways to prevent teachers to do irregularities and thus will be more careful in carrying out his work as educators. This research is intended to study supervision activities performed by principal of SD Negeri 8 Pulau Rimau. The methodology of this reseach is descriptive qualitative approach. Source of data obtained from transcript from interviews conducted to teachers and Principal of SD Negeri 8 Pulau Rimau. Technique of data collection using interview techniques, observation, and document. The results of this research show several findings: 1). The focus of supervision activities performed by principal can be identified in two things i.e supervision activities concerning the teachers’ administration and teachers’ teaching practices; 2). Supervision activity is useful for teachers to solve educational problems at the time of learning, and to provide motivation for them to improve the knowledge to become professionals in teaching and learning process; 3). Principal’s barriers in supervision consists of overlapping activities and lack of operational budget.